Photon-Pair Generation with a 100 nm Thick Carbon Nanotube Film - Lee, Kim Fook (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.